Evaluation of the physicochemical and sensory properties of roasted robusta coffee beans produced in Bataan - Santos, Isabel Raya R.
Coffee has been one of the promising commodities of the Philippines, but a decrease in coffee production was observed in the past decade. With this, various efforts have been made to improve the overall production and quality of coffee. A few studies were made regarding the different properties of various coffee in the Philippines, however, there is still a lack of study focusing on Bataan-produced coffee. This study aimed to evaluate the physicochemical (color, moisture content, aw, ρb, pH, and caffeine content) and sensory properties of Bataan roasted Robusta coffee beans at varying roasting degrees (light, medium, and dark) to serve as a guide and baseline in maximizing its quality and defining the distinct characteristics of Bataan coffee. Results from the semi-structured interview show that the general process of coffee production in Bataan consists of seven (7) steps: harvesting, drying, dehulling, sorting, roasting, grinding, and packaging. Traditional methods are used for harvesting, drying, and sorting while dehulling, roasting, and grinding are performed with machinery. Roasting significantly influenced all the physicochemical properties of Robusta coffee, where the roasting degree was observed to have an inverse relationship with color, moisture, aw, and ρb. On the other hand, caffeine content increased with the roasting degree, while pH values varied where the medium roast had the highest acidity. PCA revealed distinct clusters based on roast degree, supporting the previous findings. Strong correlations were also observed among color, moisture, ρb, aw, pH, and caffeine content, emphasizing the interdependence of these properties. The sensory evaluation through an FGD identified distinct aroma, flavor, and mouthfeel characteristics for light, medium, and dark roasted coffee samples. These profiles, which highlight the unique attributes of each roast, can be used to market and promote Robusta coffee from Bataan, Philippines.